Bioavailability studies of nutraceuticals - Ismail, Maznah; Loh, Su Peng; M. H., Waffaa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Despite increasing interest in nutraceuticals and their potential health benefit, not much is known about bioavailability of most of these nutraceutical compounds. Although they are considered dietary supplement and are subjected to a limited form of regulation, there is, however, a need to improve the efficacy and safety of these nutraceuticals. Additional research which defines the pharmacology, stability and bioavailability of these products is expected to gain strength and may offer a better understanding of their applicability in the prevention of disease conditions. This article reviews some aspects of nutraceutical bioavailability with examples from our work on the absorption studies of minerals from spirulina (Arthrospira plantensis) and gamma-oryzanol from rice bran (Oriza sativa) extract which employed human colon carcinoma (Caco-2) cell line and in vivo bioassays using animal models. Bioavailability of iron from spirulina was compared with its common source FeSo4. Using the in vitro digestion protocol in combination with Caco-2 cell culture system, spirulina showed a high iron bioavailability compared to FeSO4. The presence of other dietary factors (calcium, ascorbic acid, zinc, tannin and caffeine) was found to be not as significant as ferrous sulphate in affecting the iron uptake from spirulina. In vivo study showed that the efficacy of iron repletion in anaemic rats was enhanced in groups fed either commercial or cultured spirulina with improved haematological parameters of iron status. Further work on the behaviour and distribution of radiolabelled iron from spirulina has sown that iron 59 retained in the GIT of mice was lower in spirulina group compared to FeSO4. Bioavailability study of gamma oryzanol was similarly conducted using Caco-2 cell as in vitro system and rabbit as in vivo model with the application of different formulations of gamma oryzanol in comparison with the natural form. Both systems showed that gamma oryzanol in its natural oil was poorly absorbed. However, when converted to other formulations, gamma oryxanol bioavailability was greatly increased by as much 200 and 33 times more from the emulsion and microspheres respectively. These findings suggest that the efficacy of nutraceuticals in particular plant derived products which contain many ohytochemicals should be assessed in terms of not only their potential health benefits such as antioxidant action but also their bioavailability in order to provide a more wholesome picture of their potential.